Eye tracking and multidisciplinary studies on translation - Walker, Callum; Federici, Federico M. (Benjamins translation library, 2018)
"Through cohesive yet wide-ranging contributions focused on the rapidly growing area of eye tracking in Translation Studies, this volume provides readers with an insightful cross-section of the state of the art in this multidisciplinary field. Showcasing the great potential and challenges of this still nascent paradigm, it offers novel, practical methods and approaches to conduct ambitious, experimental studies. Through a variety of methodologically-oriented chapters and case studies, categorised into three key areas - 'Method', 'Process' and 'Product' -, the book presents some of the most up-to-date eye-tracking methods and results in Translation Studies, including experiment design, statistical and analytical approaches, the translation process, audience and reader response, and audiovisual translation. The reproducible research protocols, re-iterative approaches and ambitious triangulations of data included in this volume seek to inspire new research using eye tracking in Translation Studies by providing the necessary methodological support and ideas for new avenues of inquiry"--